2012
DOI: 10.1155/2012/837230
|View full text |Cite
|
Sign up to set email alerts
|

New Flexible Medical Compact Antenna: Design and Analysis

Abstract: Some results on embedded antennas for medical wireless communication systems are presented. Medical telemetry can advantageously assist medical diagnostics. For example, you can better locate a diseased area by monitoring temperature inside the human body. In order to establish efficient wireless links in such an environment, a special attention should be paid to the antenna design. It is required to be of a low profile, very small regardless of the working frequency—434 MHz in the ISM band, safe, and cost eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…In this paper, we propose an ultrawideband conformal loop antenna attached on the outer-wall of a capsule module with the size of 19.5 mm × 10 mm operating at 433 MHz industrial, scientific and medical (ISM) band. The simulation results show that proposed antenna has a BW −10dB of 1912 MHz (288-2200 MHz), which is a much wider than reported existing designs, and allows a much smaller capsule size except for that in [6], [10]. It was also demonstrated that the proposed antenna is robust against changes of surrounding environments such as other components in the capsule, different tissues in the digestive tract, different locations, and varying orientations inside the body.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this paper, we propose an ultrawideband conformal loop antenna attached on the outer-wall of a capsule module with the size of 19.5 mm × 10 mm operating at 433 MHz industrial, scientific and medical (ISM) band. The simulation results show that proposed antenna has a BW −10dB of 1912 MHz (288-2200 MHz), which is a much wider than reported existing designs, and allows a much smaller capsule size except for that in [6], [10]. It was also demonstrated that the proposed antenna is robust against changes of surrounding environments such as other components in the capsule, different tissues in the digestive tract, different locations, and varying orientations inside the body.…”
Section: Introductionmentioning
confidence: 85%
“…In addition to the requirement of miniaturization, the bandwidth of the antenna needs to be as wide as possible to overcome the detuning effects due to varying tissue properties through the digestive tract, as well as to realize higher data rates. According to the author's best knowledge, the smallest capsule antenna is reported for a capsule with a size of only 17 mm × 7 mm in [6] and [10], but the BW −10dB is only 17 MHz and 53 MHz, respectively. Keeping in mind the operation environment of a WCE system, these matching bandwidths are relatively narrow.…”
Section: Introductionmentioning
confidence: 99%
“…The in-body antenna needs to be fitted into a small capsule, and the bandwidth requires to be wide enough to overcome the detuning effects due to varying tissue properties throughout the GI tract. Recent research has shown embedded [24]- [33] and conformal structures [7], [9], [17], [34]- [41], [43]- [45] as promising capsule antenna types. Embedded antennas are placed inside the capsule cavity.…”
Section: B Review Of In-body Capsule Antennasmentioning
confidence: 99%
“…Cheng et al proposed a complementary split-ring resonator (CSRR) loaded 2.45-GHz patch antenna. Mahe et al employed λ\4 stepped impedance resonator along with meandering to miniaturize the microstrip antenna [42]. Recently, we reported a methodology [43] and a miniature 434-MHz antenna design [39] capable of efficient operation from all tissues with high water contents.…”
Section: Antenna Design Approachesmentioning
confidence: 99%
“…The λ/2 stepped-impedance resonator can be accurately modeled using the transmission-line-impedance equation (the derivation is given in [42]):…”
mentioning
confidence: 99%